2021
DOI: 10.1038/s41598-021-92491-7
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a new human colon cancer cell line, PUMC-CRC1

Abstract: Colorectal cancer (CRC) is one of the most common and fatal gastrointestinal cancers worldwide. Considering their diversity, the establishment of new continuous CRC cell lines with clear genetic backgrounds will provide useful tools for exploring molecular mechanisms, screening and evaluating antitumor drugs in CRC studies. Our de novo CRC cell line, PUMC-CRC1 (Peking Union Medical College Colorectal Cancer 1) was derived from a 47-year-old Chinese female patient diagnosed with moderately to poorly differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Generally, cancer has been linked to mutations in the ERBB4 gene [ 25 ], which in this study was confirmed as a highly unstable gene. No information was found on the sequenced P.Q264* missense mutation in this gene, even if this has been already sequenced in a colon cancer cell line [ 26 ]. Regarding CSF1R , as for the SNP rs386693509, no MAF is reported in the databank for this mutation, but it has been sequenced on 15 patients out of 17 in our cohort (88.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, cancer has been linked to mutations in the ERBB4 gene [ 25 ], which in this study was confirmed as a highly unstable gene. No information was found on the sequenced P.Q264* missense mutation in this gene, even if this has been already sequenced in a colon cancer cell line [ 26 ]. Regarding CSF1R , as for the SNP rs386693509, no MAF is reported in the databank for this mutation, but it has been sequenced on 15 patients out of 17 in our cohort (88.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate cell lines are selected based on the type of cancer or gene expression levels, according to the aims of the study. SW620, Caco-2, RKO, SW480, HT8, HT29, HT116, LoVo, and LS174 T cell lines are currently widely used in basic research studies on CRC ( Akashi et al, 2000 ; Vécsey et al, 2002 ; Lind et al, 2004 ; Barretina et al, 2012 ; Ahmed et al, 2013 ; Gemei et al, 2013; Mouradov et al, 2014 ; Maletzki et al, 2015 ; Boot et al, 2016 ; Berg et al, 2017 ; Mooi et al, 2018 ; Kim et al, 2020 ; Bian et al, 2021 ).…”
Section: Cellular Models Based On Intestinal Cells and Crc Cellsmentioning
confidence: 99%
“…Generally, primary culture of CRC cells involves isolating fresh tumor tissues via enzymatic treatment and culturing them in fetal bovine serum supplemented media [ 13 ]. Obtaining cell lines that can undergo stable passage is challenging; Bian et al mention that the success rate of cell line establishment from a fresh CRC tumor tissue is only approximately 10% [ 14 ]. Each 2D-cultured CRC cell line shows distinct morphological features.…”
Section: In Vitro Models Of Colorectal Cancer: From Two To Three Dime...mentioning
confidence: 99%